Adolescência: conhecimento sobre prevenção de IST/HIV/AIDS x letramento em saúde - Scopacasa, Ligia Fernandes (2017)
Adolescence is a stage in life that adds a duality between experimentation and risk. It is noted how it is necessary to carry out educational strategies with this public in the search of minimizing risk behaviors. The theme of health in literacy emerges which consists in evaluating people's ability to understand a health service-related orientation. The aim of this study was to validate the S-TOFLHA questionnaire for school adolescents, to identify the knowledge of adolescents in relation to STI/HIV/aids prevention, to analyze, through S-TOFLHA, the adolescent literacy level and compare the knowledge of adolescents in relation to the prevention of STI/HIV/aids with the degree of literacy in health. It is a study with two approaches, the first being a methodological development research and the second a correlational approach, which were divided into two phases, the first one for the validation of the S-TOFLHA instrument by the judges and the pilot test and the second by the application of the instrument validated to adolescents along with the questionnaire that addresses the adolescents' knowledge regarding the prevention of STI/HIV/aids. The sample of the judges was in a total of 22 subjects and the adolescents of the pilot test totaled 31 participants. For the second stage, the research sample was 408 adolescents. The judges answered an instrument that evaluated the objective, structure and presentation and relevance according to the Likert scale, being calculated the IVC. For the pilot test, the following statistical analysis was performed: the findings were evaluated for normality by the Shapiro-Wilk test, indicating normality. For the statistical analysis: Correlations were expressed using the Pearson correlation coefficient and the Student's T-test. For the statistical analysis of the second part, the Shapiro-Wilk test was used, indicating non-normality. For the statistical analysis: Correlations were expressed using Spearman's correlation coefficient, Mann-Whitney, Kruskal-Wallis. The ethical aspects were met and approved by COMEPE of the UFC under CAAE: 56889816.0.0000.5054. According to the findings, teacher (68.2%) was the most prevalent graduation. The main educational level of the judges was specialist (59.1) and they had at least 5 to 9 years of work with adolescents (63.63%). The validation domains were considered adequate in relation to the objective, structure and presentation and relevance according to the obtained IVC (greater than 80% agreement). The pilot test was considered relevant and there was no statistically significant correlation between the knowledge mark on STI/HIV/aids and the health literacy score (r = 0.451; p = 0.012). The adolescents presented an adequate degree of health literacy (87.4 points) and a good knowledge about STI/HIV/aids (64.7 points). There was a statistically significant correlation and difference between the variables health literacy and adolescents' knowledge about STI/HIV/aids prevention (r = 0.470; p <0.001). It was concluded that S-TOFLHA was validated for adolescents. The adolescents presented an adequate degree of health literacy and a good knowledge about STI/HIV/aids. The higher the literacy in health, the greater the knowledge of the adolescent regarding the prevention of STI/HIV/aids.